2015
DOI: 10.1039/c5ta02198g
|View full text |Cite
|
Sign up to set email alerts
|

One-step hydrothermal synthesis of monolayer MoS2 quantum dots for highly efficient electrocatalytic hydrogen evolution

Abstract: Monolayer MoS2 QDs were prepared via a facile hydrothermal process and exhibited excellent catalytic activity for the hydrogen evolution reaction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

19
171
2
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 338 publications
(199 citation statements)
references
References 43 publications
19
171
2
1
Order By: Relevance
“…For instance, MoS 2 nanosheets-coated TiO 2 nanobelt exhibited a desirable photocatalytic hydrogen reaction activity, suggesting the matched energy band of TiO 2 @MoS 2 hybrids favor the suppression of photoelectron-hole recombination (Zhou et al, 2013). When ultrathin MoS 2 nanosheets were confined to zero dimensions, the MoS 2 QDs would give rise to the interesting physical ϯ properties with abundant exposed catalytic edge sites and excellent intrinsic conductivity of monolayer structure (Gopalakrishnan et al, 2015;Ren et al, 2015). However, studies on MoS 2 QDs-based biosensing have been less reported owing to the lack of surface functional groups.…”
Section: Introductionmentioning
confidence: 98%
“…For instance, MoS 2 nanosheets-coated TiO 2 nanobelt exhibited a desirable photocatalytic hydrogen reaction activity, suggesting the matched energy band of TiO 2 @MoS 2 hybrids favor the suppression of photoelectron-hole recombination (Zhou et al, 2013). When ultrathin MoS 2 nanosheets were confined to zero dimensions, the MoS 2 QDs would give rise to the interesting physical ϯ properties with abundant exposed catalytic edge sites and excellent intrinsic conductivity of monolayer structure (Gopalakrishnan et al, 2015;Ren et al, 2015). However, studies on MoS 2 QDs-based biosensing have been less reported owing to the lack of surface functional groups.…”
Section: Introductionmentioning
confidence: 98%
“…Tafel plots of all the samples are given in Figure 4b. Commercial Pt/C electrocatalyst showed a Tafel slope of 39 mV/decade, whereas MoS 2 -commercial, MoS 2 -synthesized and MoS 2 grown over CNFs showed a Tafel slope of [45]. MoS 2 grown on Toray paper, MWCNT, and CNT/graphene showed a Tafel slope of 120, 109 and 100 mV/decade, respectively [41,46,47].…”
Section: Introductionmentioning
confidence: 99%
“…Lithium intercalated MoS2 showed a Tafel slope of 62 mV/decade [22]. Ren et al have synthesized monolayer of MoS2 quantum dots and observed a Tafel slope of 59 mV/decade [45]. MoS2 grown on Toray paper, MWCNT, and CNT/graphene showed a Tafel slope of 120, 109 and 100 mV/decade, respectively [41,46,47].…”
Section: Introductionmentioning
confidence: 99%
“…5B shows the Tafel plots for the all catalysts. The Tafel slope determined by Tafel plots andthe linear portions are fitted into the Tafel equation, h = a +b log (j0) ( a is the Tafel constant b is the Tafel slope , j0is the exchange current density), which reveals the intrinsic properties of the electrocatalyst materials [30,31]. A small Tafel slopes of 66 mV/dec for MoS2-RGO-3, which is much smaller than the Tafel slope of the MoS2 (∼162 mV/dec) and other MoS2-RGO samples (MoS2-RGO-1 ∼98 mV/dec, MoS2-RGO-2 ∼ 96 mV/dec and MoS2-RGO-4 ∼ 215 mV/dec).…”
Section: Resultsmentioning
confidence: 99%